Targeting and functional effects of biomaterials-based nanoagents for acute pancreatitis treatment - Cai, Yujie; Cao, Qian; Li, Jiannan; Liu, Tongjun (Frontiers in Bioengineering and Biotechnology, 2023)
Acute pancreatitis (AP) is a severe life-threatening inflammatory disease showing primary characteristics of excessive inflammatory response and oxidative stress. Based on the pathophysiology of AP, several anti-inflammatory and anti-oxidative stress agents have been studied. However, the low accumulated concentrations and scattered biodistributions limit the application of these agents. With the development of nanotechnology, functional nanomaterials can improve the bioavailability of drugs and extend their half-life by reducing immunogenicity to achieve targeted drug delivery. The biomaterial-based carriers can mediate the passive or active delivery of drugs to the target site for improved therapeutic effects, such as anti-oxidation and anti-inflammation for AP treatment. Other biomaterials-based nanomedicine may exhibit different functions with/without targeting effects. In this review, we have summarized the targeting and functional effects of biomaterials-based nanoagents specifically for AP treatment.